Determinants of Sharia Banks’ Efficiency In Indonesia: Panel Data Analysis - Shidiqi, Khalifany Ash; Rachmawati, Aulifah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
Nowadays, the development of Sharia Banks (SB) in Indonesia showed positive results. However, the development of SB is still slow because their competitiveness levels are far from the conventional banks, which is proven by the small amount of market shares. One of the efforts to gain competitiveness is by maintaining efficiency that it can give magnificent boost to the development. This paper aims to estimate factors that are affecting efficiency of Sharia banks in Indonesia. The use of panel data of 11 public SB from 2012 – 2016 and random effect regression illustrate how CAR, ROA, ROE, NPF, FDR and Number of Branches (NB) affect efficiency. In particular, we use Operating Expense Ratio (OER) to determine the efficiency level of Sharia Banks. The estimation finds that ROA, FDR, NB have reverse correlation toward OER, NPF has positive effect, and CAR as well as ROE are not significantly affect OER.